Gestão de defesa: o sistema de inovação no segmento de não-guerra - Franco-Azevedo, Carlos Eduardo (2013)
With the end of the Cold War and the events that took place on 'September 11', new threats have emerged, negatively impacting the perception of collective security, and imposing profound changes in the structure and mode of action of the Military of various nations. The social marginalization, drug trafficking, organized crime, environmental degradation and many other threats, have made some nations found themselves motivated to employ its armed forces primarily to combat these ills, i.e., in the 'Operations Others Than The War' (OOTW). This phenomenon has caused a up-sege in military science, as reflected in the social, political and economic, triggering a process known as 'Defense Transformation or Revolution of Military Affairs (RMA)', which is only feasible with the rupture of some traditional management models and the introduction of a new organizational culture that promotes an environment suited to the process of innovation in the Defense sector. To manage this process, there should be a sectorial innovation system of defense, which, as pointed research is fragmented and disjointed, which produces fundamentally incremental innovations and rarely disruptive ones. It is a virtual system that does not formally exist as such, but it has all the necessary infrastructure to operate as a formal system and manageable. The research, of epistemological structuralism similarities, aimed to develop a conceptual model for managing the innovation system of the Defense sector (OOTW segment), based on an subjacent structure unveiled that, covertly, support the current system. The unveiling of this structure allowed us to conclude that, in the studied field, the agents of the innovation system, acting in accordance with their interests, mobilize, consciously or unconsciously, the evaluative factors of innovation present in their organizational culture, which, along with the influence of support factors (Capital), are essential for the formation of alliances and, consequently, to the process of innovation for Defense sector (OOTW segment). As expected, the unveiling of the subjacent structure led to the realization of an accurate diagnosis of the studied system, allowing the researcher to launch a critical eye on it, which contributes to the proposition of a safe intervention in the current model. The proposed model sought to encourage also the creation, advancement and dissemination of non-technological innovations, in contrast to the current, which focuses primarily technological approach. Additionally, some measures have been suggested, in order to increase the interactions between the main actors of the system.